Non-substitutable consumption growth risk - Robert F. Dittmar; Christian Schlag; Julian Thimme (Leibniz Institute for Financial Research SAFE, 2023)
Standard applications of the consumption-based asset pricing model assume that goods and services within the nondurable consumption bundle are substitutes. We estimate substitution elasticities between different consumption bundles and show that households cannot substitute energy consumption by consumption of other nondurables. As a consequence, energy consumption affects the pricing function as a separate factor. Variation in energy consumption betas explains a large part of the premia related to value, investment, and operating profitability. For example, value stocks are typically more energy-intensive than growth stocks and thus riskier, since they suffer more from the oil supply shocks that also affect households.
Keywords: G12; E44; D81; 330; Asset pricing; consumption; cross-section of stock returns